2018
DOI: 10.6061/clinics/2018/e256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of systemic inflammation in patients being weaned from mechanical ventilation

Abstract: OBJECTIVES:The aim of this study was to evaluate systemic inflammatory factors and their relation to success or failure in a spontaneous ventilation test.METHODS:This cross-sectional study included a sample of 54 adult patients. Demographic data and clinical parameters were collected, and blood samples were collected in the first minute of the spontaneous ventilation test to evaluate interleukin (IL)-1β, IL-6, IL-8, and IL-10, tumour necrosis factor alpha (TNFα) and C-reactive protein.RESULTS:Patients who expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
5
0
7
Order By: Relevance
“…Several markers of inflammation, such as interleukin-6 (IL-6), IL-18 and C-reactive protein (CRP), have been correlated with poor prognosis in septic patients [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Specifically, IL-18, a pleiotropic pro-inflammatory cytokine with abnormal expression in sepsis and a marker of inflammasome activity, has a documented value as a prognostic indicator for the outcome of critically ill septic patients [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several markers of inflammation, such as interleukin-6 (IL-6), IL-18 and C-reactive protein (CRP), have been correlated with poor prognosis in septic patients [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Specifically, IL-18, a pleiotropic pro-inflammatory cytokine with abnormal expression in sepsis and a marker of inflammasome activity, has a documented value as a prognostic indicator for the outcome of critically ill septic patients [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…32 Previous studies have investigated the role of systemic in ammatory biomarkers to predict the extubation status in severe pneumonia patients. 35 However, to our knowledge, no previous studies had evaluated the local in ammatory biomarkers to guide the clinician in determining the extubation status of severe pneumonia patients, particularly in the right and left severely affected lung. Previous studies showed that sTREM-1, 5 alveolar macrophage, 15 IL-6, 16 IL-17, 17 CD4 and Tregs, 18 SP-A, 19 and Caspase-3 20 played a crucial role in local immunopathology (innate and adaptive immunity).…”
Section: Discussionmentioning
confidence: 99%
“…Em relação aos dados gasométricos entre GS e GI, ambos apresentaram valores semelhantes, logo não alcançaram significância estatística, alguns estudos sugerem que um baixo pH arterial, relação PaO2 / FiO2 menor que 300 mmHg e PaCO2 maior que 44 mmHg podem estar relacionados ao insucesso da extubação 2,3 . Todavia, outros estudos não encontraram valores estatísticos significantes 4,7,9 . Neste contexto pode-se levantar a hipótese do procedimento padrão hospitalar bem estabelecido e consolidado na instituição onde a pesquisa foi desenvolvida possuir um protocolo inicial para eleger pacientes ao teste de respiração espontânea, onde critérios gasométricos próximos da normalidade devem ser cumpridos.…”
Section: Discussionunclassified
“…Os testes de respiração espontânea (TRE) podem resultar em estresse cardiopulmonar e falha na extubação, uma vez que essa transição resulta em aumento das necessidades de energia muscular respiratória de acordo com o grau de sobrecarga respiratória (estresse respiratório) e a resultante demanda aumentada de oxigênio, que levam ao aumento do débito cardíaco (estresse cardiovascular). Este estresse cardiopulmonar induz inflamação sistêmica, através de diferentes sistemas biológicos associados ao sistema nervoso simpático e à liberação de catecolaminas 4 .…”
Section: Introductionunclassified
See 1 more Smart Citation